METHOD FOR OBTAINING ADDITIVES FROM WASTE POLYMERIC MATERIALS FOR BITUMEN - Umarov Shodiljon Abdug ‘ofurovich; Abobakirova Zebuniso Asrorovna (Journals Park Publishing, 2022)
The basic purpose of bitumen of a mineral powder as be completed of bitumen is to translate volumetric bitumen in a film status. In such status the viscosity and durability of bitumen raises. The important value has that circumstance, that the application of the activated polymeric powders essentially reduces the charge of bitumen and completed.
Keywords: varnishcolourful, bitumen, аsphaltconcrete, mineral powder mixed knitting, way of reception